2021
DOI: 10.1093/pm/pnab296
|View full text |Cite
|
Sign up to set email alerts
|

The External Oblique Intercostal Block: Anatomic Evaluation and Case Series

Abstract: Study Objective We report a modified block technique aimed at obtaining upper midline and lateral abdominal wall analgesia: the external oblique intercostal (EOI) block. Design A cadaveric study and retrospective cohort study assessing the potential analgesic effect of the EOI block. Setting Cadaver lab and operating room. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 18 publications
0
46
0
1
Order By: Relevance
“…The potential mechanism of this technique has been proposed by Elsharkawy et al., who showed staining of both the anterior and lateral cutaneous branches of T7 to T10 with only one injection required in fresh frozen cadavers [3]. The same group also showed consistent dermatomal blockade of the same nerves at both the midline and the anterior axillary line in a series of 22 patients who underwent various upper abdominal procedures [3]. We reproduced a similar dermatomal sensory coverage, with evidence of blockade of both anterior and lateral branches of upper thoracoabdominal nerves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential mechanism of this technique has been proposed by Elsharkawy et al., who showed staining of both the anterior and lateral cutaneous branches of T7 to T10 with only one injection required in fresh frozen cadavers [3]. The same group also showed consistent dermatomal blockade of the same nerves at both the midline and the anterior axillary line in a series of 22 patients who underwent various upper abdominal procedures [3]. We reproduced a similar dermatomal sensory coverage, with evidence of blockade of both anterior and lateral branches of upper thoracoabdominal nerves.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst various FPBs have been described for truncal analgesia, until recently, there has been a paucity of evidence regarding their effectiveness to provide analgesia for supra‐umbilical and subcostal incisions. The external oblique intercostal (EOI) block is a recently described FPB which has been shown to cover the anterior and lateral upper abdominal wall [3]. It provides analgesia for the upper abdomen without the systemic effects of sympathetic blockade, and without affecting motor and bladder functions.…”
Section: Introductionmentioning
confidence: 99%
“…EOI block is a modified block technique for upper midline and lateral abdominal wall analgesia. Elsharkawy et al [10] demonstrated the potential mechanism of this technique with a cadaveric study reporting consistent staining of both lateral and anterior branches of intercostal nerves T7-T10. The fact that the EOI block used in the present case series reduces opioid consumption to almost zero may indicate that it will soon come very close to being the first choice as an opioid protective block.…”
Section: Discussionmentioning
confidence: 99%
“…The EOI block is described as between the sixth intercostal space and the external oblique muscle slightly lateral to the midclavicular line, whereas the superficial TAPA is three ribs caudal between the ninth to tenth costal cartilages and the external oblique muscle at the costal margin. 14,15 Likewise, the deep injection point of the TAPA is the same anatomical location as the subcostal TAP. The main difference is the description of the subcostal TAP includes hydrodissection while advancing the needle parallel to the costal margin.…”
mentioning
confidence: 99%
“…Le bloc EOI est de ´crit comme se situant entre le sixie `me espace intercostal et le muscle oblique externe le ´ge `rement late ´ral a `la ligne mid-claviculaire, tandis que le TAPA superficiel est situe ´sur trois co ˆtes de manie `re caudale entre le neuvie `me et le dixie `me cartilage costal et le muscle oblique externe a `la marge costale. 14,15 De me ˆme, le point d'injection profond du TAPA est situe áu me ˆme emplacement anatomique que le TAP sous-costal. La diffe ´rence principale est que la description du TAP sous-costal inclut l'hydro-dissection tout en avanc ¸ant l'aiguille paralle `lement a `la marge costale.…”
unclassified